KETERKAITAN LEADER MEMBER EXCHANGE (LMX), JOB PERFORMANCE, DAN WORK ENGAGEMENT - Joko Pitoyo, Didik (Widya Warta, 2018)
The purpose of this study was to analyze the influence of work engagement as intervening variable relationship between leader member exchange and job performance. This study used a quantitative research method.The samples used in this study were 213 people in the PT Kusumaputra Santosa Karanganyar. The data analysis technique was path analysis. The results of this study were:Â  a) LMX had significant effect on job performance. b) LMX and work engagement had significant effect on job performance. c) Work engagement was able to be a mediating variable and was expressed as a partial mediating variables (partial mediation). This was because the influence of leader member exchange variables for job performance was remained significant even after entering work engagement variable into the regression model but the regression coefficient was declined.